The Effect of Production and Price on the Income of Seaweed Farmers in Tadui Village, Mamuju District - Alpianto, Azman; Rusli; Mappigau, Ernawaty (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to analyze the influence of production and price on the income of seaweed farmers in Tadui Village, Mamuju District. Seaweed is a leading commodity in the fisheries and agriculture sectors, which plays an important role in supporting food security, industrial raw materials, and exports. A quantitative approach is used with the help of the SPSS application to identify the relationship between independent variables (production and price) to dependent variables (income). Data was collected through a survey of seaweed farmers using purposive sampling techniques. The results of the analysis show that production and price variables partially and simultaneously have a significant influence on farmers' income. Production has a positive influence, where each increase in production increases farmers' income significantly. Prices also have a significant impact, showing the importance of price stability in improving farmers' welfare. These findings underscore the need for policies that support increased productivity and seaweed price stability to encourage economic growth of coastal communities in Tadui Village. Optimization of cultivation technology and government intervention in price stabilization are the main recommendations of this study.